Cooperative in Malaysia / Amariah Hanum Hussin - Hussin, Amariah Hanum (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Cooperatives are people-centred enterprises owned, controlled, and run by and for their members to realise their common economic, social, and cultural needs and aspirations. A cooperative also known as a non-profit and people-centred enterprise possessed, operated, and managed by members. According to ICA, 2019, Cooperative brings communities collectively in a representative and equivalent manner to realize a common economic, community, and cultural need and desire. In addition, Mahazril 'Aini et al. (2012) and Ortmann and King (2007) stated that cooperatives are established to improve the well-being of the members, eradicate poverty, and serve as an alternative platform to distribute the national wealth amongst the people. Indirectly, the cooperatives play a significant role in elevating the socio-economic and well-being of members of communities and substantially contribute to the nation's Gross Domestic Product (GDP) (Zakaria, et al., 2022). In Malaysia, cooperative plays a third crucial roles after the public and private sectors in driving the nation's economic growth. Indeed, Malaysia is home to numerous cooperatives Yuhertiana, I (2022). The role of cooperatives is also being rapidly recognized for their contributions to the Malaysian economy, both socially and economically Othman, (2013) and Hashim et all (2017). Therefore, the government seen cooperative as another crucial vehicle to drive and boost up the development and growth of the countries' economic.